Watching the watchdog: an analysis of Nigerian media performance during the 2011 general elections (2014)
The general elections in 2011 in Nigeria took place amidst local and international skepticism about the competence of the ruling party to organize peaceful, free, fair and credible election. The election ended up being universally acclaimed as credible. The mass media played very important role in covering and reporting the election. Most of the media coverage was however concentrated on urban locations while the rural areas and the grassroots were largely neglected. The new media played prominent role during the election. Social media were adequately exploited by the electorates to share information and prevent irregularities that could have smeared the election. This trend largely contributed to the success of the election. Nigeria media appears to be maturing and gradually assuming its responsibilities in nurturing democracy, its institutions and practices in the country. With the assistance of the civil society, the media could divest itself of the ulterior influences that prevents it from providing appropriate leadership in growing democracy. The extent to which it could sustain its independence and improve the quality of its human resources would however determine how relevant and credible it would continue to be in the political firmament